Genotype by environment interaction and yield stability in sugarcane (2017)
Genotype by environment interaction (GEI) reduces the association between phenotype and genotype which result in relative ranking and stability differences of genotypes across environment. The objectives of this research were (i) to select sugarcane genotypes of high yield and stable (ii) to study the interrelationships among various parametric and no parametric stability statistics. Seventeen experimental genotypes and three check cultivars of sugarcane were evaluated at seven environment using randomized completely block design. Methodologies based on analysis parametric (Regression-bi-S2di, Shukla variance, Ecovalence-W, Coefficient of variation-CV, index of Lin and Binns-PI and AMMI value) and non-parametric statistics (Nassar and Huehn- Si(1), Si(2), Si(3), Si(6), Kang-RS, Fox-TOP, and Thennarasu- NPi(1) , NPi(2), NPi(3), NPi(4)) were used for Ton of Pol per hectare (TPH). Genotypes and environment showed high significant difference (P0.01) while GEI was significant (P0.05). The parametric stability analysis identified the genotypes V99-236 and V00-50 as the most stable and high TPH. With non-parametric statistics were identified the genotypes V00-50, V99-236 and V98-120 as most stable. The analysis distinguished two groups of statistics using biplot: the first group (G1) formed by PI, CV, ASV, TOP, Si(3), Si(6), NPi(2), NPi(3) and NPi(4) statistics were located under the concept of dynamic stability since they are associated with TPH. The other group (G2), formed by Shukla, W, S2di, bi, RS, Si(2), Si(1), NPi(1) statistics, fell within the static concept. Finally, genotypes V99-236 and V00-50 can be recommended as the most stable genotype in terms of both, stability and TPH.